2008
DOI: 10.1172/jci34316
|View full text |Cite
|
Sign up to set email alerts
|

Serotype-dependent packaging of large genes in adeno-associated viral vectors results in effective gene delivery in mice

Abstract: Vectors derived from adeno-associated virus (AAV) are promising for human gene therapy, including treatment for retinal blindness. One major limitation of AAVs as vectors is that AAV cargo capacity has been considered to be restricted to 4.7 kb. Here we demonstrate that vectors with an AAV5 capsid (i.e., rAAV2/5) incorporated up to 8.9 kb of genome more efficiently than 6 other serotypes tested, independent of the efficiency of the rAAV2/5 production process. Efficient packaging of the large murine Abca4 and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
218
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(235 citation statements)
references
References 50 publications
4
218
2
4
Order By: Relevance
“…56,57 Use of appropriate AAV vectors may prevent or reduce such anomalous reorganizations within the inner nuclear layer, potentially enhancing the effectiveness of other therapies such as cellular or bionic implants. 57 Finally, new vector constructs, different modes of delivery, 24,25 and the isolation and modification of different serotypes 7,58-62 will lead to novel vectors that have greater packaging capacity 33,63 and cell specificity, and may even further minimize immunological sequelae following therapeutic application.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Use of appropriate AAV vectors may prevent or reduce such anomalous reorganizations within the inner nuclear layer, potentially enhancing the effectiveness of other therapies such as cellular or bionic implants. 57 Finally, new vector constructs, different modes of delivery, 24,25 and the isolation and modification of different serotypes 7,58-62 will lead to novel vectors that have greater packaging capacity 33,63 and cell specificity, and may even further minimize immunological sequelae following therapeutic application.…”
Section: Discussionmentioning
confidence: 99%
“…Although large genes can be delivered efficiently to the RPE using lentiviral vectors, delivery of large genes (such as ABCA4 in Stargardt's disease) to photoreceptor cells is more difficult to achieve. Recent progress suggests that this challenge can be addressed by improvements in the capacity of rAAV vectors 18 or in photoreceptor targeting by lentiviral vectors. 22 Although it is important that results of the first clinical trials are interpreted in an appropriately balanced fashion without raising expectations disproportionately, the first findings certainly offer hope to many thousands of individuals with inherited blindness for which no treatment is currently available.…”
Section: Challenges For Gene Therapy Of Inherited Retinal Diseasementioning
confidence: 99%
“…Traditionally considered to be limited by a relatively small packaging capacity, the possibility that the rAAV2/5 capsid can incorporate up to 8.9 kb of genome greatly expands the therapeutic potential of this vector system to include applications such as Stargardt's disease and Usher's syndrome. 18 Lentivirus-based vectors are attractive candidates for ocular gene transfer because of their large genomic capacity and their ability to stably transduce non-dividing cell populations. Lentiviral vectors mediate efficient sustained expression in the retinal pigment epithelium, and variable expression in photoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Often these reasons are entirely practical; for example, the ABCA4 gene 93 currently cannot be comfortably accommodated within AAV, which is the only vector that can currently deliver transgenes reliably to the photoreceptor cells. Some studies have suggested that the corresponding condition, Stargardt disease, may be very amenable to treatment, 94,95 but until a reliable method to transfer large genes to the photoreceptor cells has been developed, further progression of this therapy to the clinic is unlikely. A second common problem for the development of gene therapy is the lack of appropriate animal models.…”
Section: Discussionmentioning
confidence: 99%